2018
DOI: 10.1108/vjikms-01-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

Employee perceptions of fairness toward IoT monitoring

Abstract: Purpose This paper aims to explore Internet of Things (IoT)-enabled monitoring in a multi-national petrochemical organization in Qatar and finds that the technology does not negatively influence employee perceptions of fairness, challenging current propositions on monitoring and highlighting the emerging role of culture, competition and paradoxical leadership in moderating the relationship between IoT-enabled monitoring and perceptions of fairness. Design/methodology/approach The authors adopted qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…IoT is a more advanced idea of the internet that connect almost everything, starting from electronic devices to people, products and machinery (Ramakrishnan and Ma, 2018). IoT plays a vital role and improves the quality of human life in a different domain (Al-Hitmi and Sherif, 2018;Rathore et al, 2016). IoT-based information services help to mix information and material flows and can optimize SCM (Papert and Pflaum, 2017;Rymaszewska et al, 2017).…”
Section: Internet Of Things Servicesmentioning
confidence: 99%
“…IoT is a more advanced idea of the internet that connect almost everything, starting from electronic devices to people, products and machinery (Ramakrishnan and Ma, 2018). IoT plays a vital role and improves the quality of human life in a different domain (Al-Hitmi and Sherif, 2018;Rathore et al, 2016). IoT-based information services help to mix information and material flows and can optimize SCM (Papert and Pflaum, 2017;Rymaszewska et al, 2017).…”
Section: Internet Of Things Servicesmentioning
confidence: 99%
“…HR professionals can play an important role by encouraging an honest and open discussion about what motivates managers to adopt such tools. Such a discussion will help all stakeholders to explore if the use of monitoring will serve the company and employees well and clarify how the captured data will be used (Al-Hitmi and Sherif, 2018). In some cases, HR departments may themselves initiate the debate about monitoring, especially when the data that could be generated are viewed as supporting HR processes (related to development, appraisal and promotions rounds).…”
Section: Stepping In and Stepping Up: Recommendations For Hrmentioning
confidence: 99%
“…All current and future employees need to be informed that monitoring will be used and in what form. All managers and employees need to receive training and have access to various feedback options for employees and to evaluate these new initiatives (Al-Hitmi and Sherif, 2018; Jeske and Santuzzi, 2015). Some monitoring initiatives may need to be readjusted over time, so there need to be channels and means to collect this information.…”
Section: Stepping In and Stepping Up: Recommendations For Hrmentioning
confidence: 99%
“…Such research has found that managers are more likely to do secret monitoring when they have a high dependence on their employees and their trust level is low (Alge et al, 2004). Perceptions of electronic monitoring can be a function of the perceived fairness of the system and employee performance (Moorman, & Wells, 2003), the role of culture, job competition, consistency, prior experience with monitoring, time to deal with monitoring problems, and amount of control desired (Al-Hitmi & Sherif, 2018), policy violations (Zweig, & Scott, 2007), perceived privacy violations, procedural justice, leave intentions (Hung-Yue, 2018), and perceived organizational justice (Stanton, 2000). Prospect theory was chosen as the lens of analysis for this research as it appears to relate to the rationale for electronic notifications and no notifications.…”
Section: Literature Reviewmentioning
confidence: 99%